2015
DOI: 10.1088/1367-2630/17/8/083020
|View full text |Cite
|
Sign up to set email alerts
|

Quantum turnstile operation of single-molecule magnets

Abstract: The time-dependent transport through single-molecule magnets coupled to magnetic or nonmagnetic electrodes is studied in the framework of the generalized master equation method. We investigate the transient regime induced by the periodic switching of the source and drain contacts. If the electrodes have opposite magnetizations the quantum turnstile operation allows the stepwise writing of intermediate excited states. In turn, the transient currents provide a way to read these states. Within our approach we tak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…There have been several studies of magnetic exchange interaction and the possibilities for electrical control of the interaction and spin transport [39][40][41][42][43][44]. Under non-equilibrium conditions, magnetic molecules show signatures of intrinsic anisotropic exchange interactions that can be used to control molecular spin [41,45], something that may lead to read-and-write capabilities with currents in spintronics devices [46][47][48]. Non-equilibrium studies of transport properties have, moreover, suggested that vibrations coupled to the spin degrees of freedom may induce electrical currents that can provide interesting properties for, e.g., mechanical control of single magnetic molecules [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies of magnetic exchange interaction and the possibilities for electrical control of the interaction and spin transport [39][40][41][42][43][44]. Under non-equilibrium conditions, magnetic molecules show signatures of intrinsic anisotropic exchange interactions that can be used to control molecular spin [41,45], something that may lead to read-and-write capabilities with currents in spintronics devices [46][47][48]. Non-equilibrium studies of transport properties have, moreover, suggested that vibrations coupled to the spin degrees of freedom may induce electrical currents that can provide interesting properties for, e.g., mechanical control of single magnetic molecules [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant class of transport phenomena which can be modeled and understood within the GME method is the electron pumping through QDs with tunable-barriers (see e.g., the recent review [ 57 ]). In this context we investigated the transient response of a quantum dot submitted to a sequence of rectangular pulses applied at the contact to the input [ 58 ] and the turnstile protocol for single-molecule magnets [ 59 ].…”
Section: Many-body Effects In the Transient Regimementioning
confidence: 99%
“…In the present work we rely on the generalized master equation (GME) method which was previously used to study the turnstile regime of single-molecule magnets 27 and recently extended for hybrid systems such as NEMS or cavity-QD systems 28 . The model Hamiltonian embodies both the electron-electron interaction within the electronic subsystem and the spin degree of freedom.…”
Section: Introductionmentioning
confidence: 99%